How India Leads the South Asian Regional Security Complex - Dika Atmawati Sukaedi; Ligar Yogaswara (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2024)
Abstract This research explores the regional security dynamics of South Asia through the lens of the Regional Security Complex (RSC) theory, developed by Barry Buzan and Ole Wæver. The research provides a comprehensive geopolitical analysis focusing on India's maritime interests and the broader regional landscape, encompassing both maritime and land-based security aspects. By employing Social Network Analysis (SNA), the study uncovers India’s position as a dominant regional power, with Bhutan identified as the most vulnerable state and the Maldives distinguished as a unique entity with no military forces but significant economic growth driven by tourism. The research also includes a detailed examination of the regional security landscape, highlighting key factors such as military expenditure, energy resources, trade flows, and economic growth across South Asian countries. Geographic visualizations are utilized to map these variables, revealing intricate patterns of interdependence and vulnerability. The study extends beyond maritime strategies to analyze how India’s military and economic influence shapes regional stability. This dual approach offers a nuanced understanding of South Asia’s security environment, demonstrating how both maritime and terrestrial dimensions interplay to affect regional dynamics and contribute to international stability. Through this analysis, the study illustrates the relevance of the RSC theory in addressing complex security challenges in the South Asian context.